Transistors fabricated using the single crystals of [8]phenacene1. Issue 28 (28th July 2015) - Shimo, Yuma; Mikami, Takahiro; Murakami, Hiroto T.; Hamao, Shino; Goto, Hidenori; Okamoto, Hideki; Gohda, Shin; Sato, Kaori; Cassinese, Antonio; Hayashi, Yasuhiko; Kubozono, Yoshihiro
<x xml:space="preserve">Abstract</x> Field-effect transistors have been fabricated using [8]phenacene single-crystals, showing the maximum μ value of 8.2 cm2 V−1 s−1. The CMOS inverter circuit has also been fabricated.